Factors of Electronic Word of Mouth (E-WOM) influencing on information adoption f online consumers in Vietnam’s cosmetic sector - Do, Minh Tu (H. : ĐHQGHN, 2020)
The paper found relevance, timeliness, accuracy, comprehensiveness and source trustworthiness to be the most effective components of the argument quality construct and source credibility construct of the research model, making them key influencers of information adoption.